Implementation of Deterministic and Multimineral Method in Petrophysical Analysis for Identifying Low Resistivity Reservoir in Tesla Field, Air Benakat Formation, South Sumatera Basin - Saroji, Sudarmaji; Trihapsari, Wandia Mellani; Trisna, Muhammad Destrayuda (Graduate School of Universitas Syiah Kuala, 2024)
The Tesla field is located in the South Sumatra Basin, where there is the Air Benakat Formation, with the constituent rocks being dominated by alternating sandstone and claystone so that it is a shaly sand environment with the potential to become a low-resistivity hydrocarbon reservoir. Hydrocarbon reservoirs generally have a resistivity log value of more than 10 m; when a hydrocarbon reservoir has a low-resistivity value between 0.5 - 5 m, it is referred to as a low-resistivity hydrocarbon reservoir. Initially, deterministic analysis was carried out to calculate the petrophysical parameters of the potentially low-resistivity reservoirs. However, the results show a low validation value of petrophysics parameters, such as effective porosity and water saturation, when compared to the DST data, so a multimineral analysis is carried out to increase the validation value of the petrophysical parameters. The use of the multimineral method has produced the petrophysics parameter closer to DST Data when compared to the petrophysics parameter produced by the deterministic method in Tesla Field. The formation analysis shows that the low resistivity reservoir in the Tesla Field is caused by the grain size of the sandstone, which is very fine so that it can bind water significantly (irreducible water), abundant shale content, and distributed by lamination of shale, dispersed shale, and structural shale as well as the presence of conductive glauconite minerals.